2020
DOI: 10.1108/mrr-01-2020-0026
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of emerging market professional service firm success: the role of internal firm competencies and capabilities

Abstract: Purpose The purpose of this study is to investigate the effects of emerging market professional service small and medium-sized enterprises’ (PSF SME) internal competencies and capabilities on their ability to establish relationship value among clients and achieve superior financial performance. This study addresses the paucity of research on emerging market PSF SMEs and their ability to build value for their clients. Design/methodology/approach Data were collected from 251 senior managers or owners of PSF SM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 67 publications
3
18
0
Order By: Relevance
“…This research value is the more in-depth exploration of the generally confirmed relationship between human capital and innovativeness (Kucharska, 2021a;Mathew et al, 2021;Wang, 2021).…”
Section: Discussionmentioning
confidence: 95%
“…This research value is the more in-depth exploration of the generally confirmed relationship between human capital and innovativeness (Kucharska, 2021a;Mathew et al, 2021;Wang, 2021).…”
Section: Discussionmentioning
confidence: 95%
“…However, critical scholars contend that this is a reflection of the imperialist mind-set adopted in global PSFs and that greater attention should be paid to peripheral offices (Boussebaa, 2015a; Boussebaa et al , 2012). Studies on PSFs from emerging markets are growing in number and show that these firms rely on different performance drivers (Mathew et al , 2020; Radulovich et al , 2018). If confirmed, the recent shift towards alternative research settings promises a more holistic understanding of international PSFs.…”
Section: Resultsmentioning
confidence: 99%
“…Professionals are typically highly educated and experienced in their field, possessing strong relationships with their individual customers. Thus, professional service firms are often highly reliant on individual professionals to assess customer needs and create value in the customer relationship (Greenwood et al, 2005;Jensen et al, 2010;Løwendahl et al, 2001;Mathew et al, 2020).…”
Section: Characteristics Of Professional Services Strengthening the E...mentioning
confidence: 99%
“…While the findings of the present study are well in line with previous research, it contributes unique and detailed explanations of how the embeddedness of individual expertise unfolds as a part of the service exchange within business relationships. This allows for a more detailed understanding of the relationship management practices that are essential to building longterm customer relationships, which requires focusing on strengthening the role of human capital and leveraging the innovativeness and service capabilities within the relationship (Mathew et al, 2020).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation